Intention to practice waste separation at source among households in Putrajaya, Malaysia - Md Ismail, Siti Aishah (2019)
In Malaysia, the public concerns on the effects of not separating waste for recycling, the sense of responsibility in managing waste properly as well as their mentality towards cleanliness is still very low. The widespread and open dumping in Malaysia had caused the landfill site worsening while source separation for recycling is at a minimal. Moreover, the generation of municipal solid waste has increased more than 91% over the past decade and the biggest contributor to waste generation was city dwellers of the urban country which constituted more than 65% of the total population. The households are the initial sources of solid waste and became the country's main generator of municipal solid waste (MSW). It was found that promoting recycling and waste separation at the household level as a good method to reduce the amount of waste generated, costs of waste collection and raised public health. Therefore, households are encouraged to engage in waste separation at source. Thus, it is important to understand what drives household intend to practice waste separation at source before any program or campaign on waste separation are implemented.